Meristic characteristics of gobiid fishes (family gobiidae) in Lake Mainit, Surigao del Norte - Escarlos, Donna Veda T. (2009)
Meristic characteristics of goby fishes in Lake Mainit were described. These characters were also used to determine any variation among the subgroups and groups of fishes. Fishes were collected and subsequently treated as group 1, 2, 3 respectively. Each group was further divided into subgroups based on color patterns. A total of twelve characters namely, dorsal fin rays, anal fin rays, pelvic fin rays, pectoral fin rays, scales at the lateral line, scales above and below the lateral line, caudal peduncle scales, predorsal scales, and gill rakers at the upper and lower limb were used to describe the fishes. Goby fishes in Lake Mainit are characterized by the following features. VI+1,9-10 dorsal fin rays, 1,9-10 anal fin rays, 17-20 pectoral fin rays, I,5pelvic fin rays, 12-17 caudal fin rays, 45-57 scales in the lateral line, 6-10 scales above the lateral line, 9-14 scales below the lateral line, 16-27 scales at the caudal peduncle, 10-20 scales, and 14-20 total gill rakers. Among subgroups, analysis of variance revealed significant difference in the mean number of the second dorsal fin rays in Group 1, pectoral fin rays in Group 2, index for fin rays and scales in group 3. On the other hand, among the three groups, the number of caudal fin rays, pectoral fin rays, scales above and below the lateral line, caudal peduncle scales, and predorsal scales, and index for fin rays and scales showed significant difference. Results of the T-test for the gill rakers also showed significant difference between Groups 2 and 3. Meristic characters that revealed significant difference can be useful in separating populations of goby fishes in Lake Mainit. The data rejected the null hypothesis of a single population of goby fishes in the area